Buried in the Archives – Medieval Graves at the Dominican Convent of St Olaf in Turku, Finland - Visa Immonen (Glossa - The Finnish Society for Medieval Studies, 2022)
The medieval Dominican convent of St Olaf in Turku, Southwest Finland is a prime example of a site documented deficiently during nineteenth- and twentieth-century excavations. The analysis of the burials discovered in the convent area is used as a case study of the limitations and possibilities of using such problematic archive material. Examining of the old documentation shows that the burials concentrate in the northern parts of the plots 1 and 2 Kaskenkatu Street. This is the area where the church and the adjacent churchyard of the convent must have been located. In addition to simple burials made in pits, and graves with coffins of wood, one distinctive brick-lined grave, containing a coffin covered with leather, is known from the site. The most interesting and a relatively common feature of the graves in Turku is the diversion from the traditional east–west orientation. After the initial reconstruction of the fieldwork data, the monastic burials are contextualised with the help of modern scholarship and reference material.